Analisis Kontrol Masyarakat terhadap Penegak Hukum pada Trend No Viral No Justice dalam Mewujudkan Keadilan - Sihaloho, Hasiholan; Sudarto, Sudarto (LITERATUS, 2025)
The rapid advancement of digital technology has transformed social dynamics, particularly in law enforcement oversight in Indonesia. The phenomenon of "No Viral No Justice" illustrates how public participation through social media platforms such as Twitter, Facebook, and TikTok can significantly influence legal processes. This study analyzes the role of social control exercised by society over law enforcement agencies within the "No Viral No Justice" trend, aiming to achieve justice. The research employs normative juridical methods, supported by case studies of several viral legal cases in Indonesia. The findings reveal that while public pressure through social media often compels authorities to respond promptly and transparently, this phenomenon also exposes weaknesses in conventional law enforcement systems. Some legal cases receive attention only after becoming viral, creating the risk of unequal legal treatment. Furthermore, challenges such as insufficient evidence, procedural delays, and external pressures complicate the pursuit of objective justice. The study concludes that although "No Viral No Justice" serves as an effective mechanism for accelerating law enforcement, it must be balanced with procedural fairness, accurate information dissemination, and judicial independence to prevent distortions of justice